Sudden Infant Death Syndrome a Case Report - İnanıcı, Mehmet Akif and Yorulmaz, Coşkun and Cantürk, Nergis (The Bulletin of Legal Medicine, 2001)
In this study, sudden and unexpected death in a 3-month-old infant was reported. Deaths of infants younger than 1-year-old for whom a thorough postmortem examination failed to reveal an adequate cause of death constitute the “Sudden Infant Death Syndrome” (SIDS). In developed countries, SIDS is one of the most common cause of death in postneonatal infants, but SIDS is being undetermined due to insufficiency in crime scene investigation and not explored with the same autopsy protocol in all cases, in our country. Keywords: Sudden infant death syndrome, child deaths, autopsy